Overcoming Barriers: A Study on Family Experiences and Treatment Adherence in Congenital Talipes Equinovarus in Kutch District, Gujarat - Vishal Pushkarna; Daxesh J Patel; Tej S Rudani (Journal of Orthopedics and Joint Surgery)
Background: The Ponseti method is widely recognized as the gold standard for managing congenital clubfoot, offering an effective, low-cost alternative to surgical interventions. This method involves a series of plaster casts, a percutaneous Achilles’ tenotomy, and the use of a Mitchell Ponseti brace, allowing for nonhospital-based care that supports family integration. However, this approach introduces challenges related to adherence to the home-based protocol. Aim: This study aims to assess the level of awareness and understanding among primary caregivers of children undergoing Ponseti method of treatment. It examines caregivers’ knowledge of congenital clubfoot, their beliefs and compliance with the treatment regimen, and the barriers they encounter during the process. Materials and methods: A comprehensive questionnaire consisting of 41 items, developed by Nogueira et al., was utilized to gather data from families who had either completed the Ponseti method treatment or were in the midst of it. The survey sought to capture detailed insights into caregivers’ experiences and perceptions. Results: The study included responses from 217 families. Findings indicated that the cast phase of treatment was perceived as particularly challenging, while the brace phase was generally considered more tolerable. A majority of 190 families reported that the tenotomy procedure was less difficult than initially expected. Despite the prevalent anxiety associated with the diagnosis, this did not adversely affect the families’ adherence to the treatment protocol. The analysis of open-ended responses underscored that a positive relationship with healthcare providers was instrumental in supporting daily adherence and achieving optimal treatment outcomes. Conclusion: The Ponseti method is positively evaluated by families, who generally regard it as an effective treatment despite its inherent challenges. Caregiver anxiety regarding the diagnosis does not significantly compromise treatment adherence or outcomes. The study highlights the importance of maintaining strong, supportive relationships between families and healthcare providers to enhance compliance and ensure successful management of congenital clubfoot.